2015
DOI: 10.1186/s13045-015-0121-9
|View full text |Cite
|
Sign up to set email alerts
|

Local administration of a novel Toll-like receptor 7 agonist in combination with doxorubicin induces durable tumouricidal effects in a murine model of T cell lymphoma

Abstract: BackgroundConventional chemotherapy and radiotherapy for the treatment of lymphoma have notable drawbacks, and passive immunotherapy using a monoclonal antibody is restricted to CD20-positive B cell lymphoma. Therefore, new treatment types are urgently required, especially for T cell lymphoma. One type of new antitumour therapy is the use of active immunotherapeutic agents, such as agonists of the Toll-like receptors (TLRs), which facilitate the induction of prolonged antitumour immune responses.MethodsWe have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 26 publications
0
44
0
Order By: Relevance
“…Intratumoral administration of SZU-101 increased the efficacy of doxorubicin, and improved tumor clearance in a T-cell lymphoma mouse model. The new combination of SZU-101 and doxorubicin administered intratumorally induced high cytokine production and improved cytotoxic T cell response, leading to the eradication of local and distal tumors in tumorbearing mice[113]. Gao et al demonstrated the enhancing tumor…”
mentioning
confidence: 99%
“…Intratumoral administration of SZU-101 increased the efficacy of doxorubicin, and improved tumor clearance in a T-cell lymphoma mouse model. The new combination of SZU-101 and doxorubicin administered intratumorally induced high cytokine production and improved cytotoxic T cell response, leading to the eradication of local and distal tumors in tumorbearing mice[113]. Gao et al demonstrated the enhancing tumor…”
mentioning
confidence: 99%
“…Recently, we have reported the synthesis of a novel TLR 7 agonist, SZU-101, and its use in combination with doxorubicin for cancer therapy. This combination induced durable tumoricidal effects in a murine model of T cell lymphoma11. We have also found that conjugating OCT4 protein to this agonist produces a vaccine that effectively and safely prevents tumor growth in mice12.…”
mentioning
confidence: 61%
“…In a previous study, our group used SZU-101 to treat tumors in a murine model of T cell lymphoma. SZU-101 could activated TLR7 NF-ÎșB signaling in a TLR7-specific system at a low concentration of 1 ”M after 6 h of stimulation in vitro (15). The anticancer therapies given directly into tumors may be more effective than given systemically, because local therapies could overcome natural suppressive factors in the tumor microenvironment, and induce systemic antitumor immunity (39).…”
Section: Discussionmentioning
confidence: 99%